Community Based Tourism Development Strategy - Arma Arman; Muh. Nur Yamin; Bakhtiar (Fakultas Ilmu Sosial dan Hukum, 2024)
Community Participation-Based Tourism Development Strategy (Study on Hutan Pinus Bulu This research aims to determine the tourism development strategy of the Hutan Punus Bulu Tanah based on community participation in Mattampawalie Village. To achieve this goal, the researchers used data collection techniques through documentation, observation, and interviews. Community participation-based tourism in the Hutan Pinus Bulu Tanah tourism, Bone Regency. The result of this study indicate that the tourism development strategy of the Hutan Pinus Bulu Tanah is based on community participation. The Mattampawalie Village community who are members of the Koperasi Serba Usaha (KSU) Labongke, which is a tourism management institution, have fully participated at every stage of partiscipation. The results of the SWOT analysis carried out can be ascertained that the Hutan Pintus Bulu Tanah tourism needs to implement an aggressive growth strategy for the Growth Oriented Strategy, because it is in an area of ​​strength and opportunity. Aggression must be done as much as possible, in order to increase growth and achieve maximum progress. The need to follow market developments, so that they can continue to survive in the competition and take a participatory approach to the community and government so that a more harmonious relationship can be established, mutual trust in each other and can build good cooperation.